EKSISTENSI MEDIA SOSIAL INSTAGRAM SEBAGAI SARANA PROMOSI DI PERPUSTAKAAN UNIVERSITAS ISLAM NEGERI IMAM BONJOL PADANG - Nofita Sari, Shinta; Marajari, M.Rinaldo (UIN Imam Bonjol Padang, 2024)
This writing was carried out at the UPT Library of UIN Imam Bonjol Padang. This writing discusses the existence of Instagram social media as a promotional tool at the Imam Bonjol Padang State Islamic University (UIN) Library. The purpose of this writing is to find out what activities on Instagram social media are promotional activities. The method used in this writing is qualitative research with a literature study approach. The results of this research are social media Instagram, various promotional activities carried out by UPT UIN Imam Bonjol Padang Library, namely various activities such as: 1) Information on the latest collections 2) Thematic events 3) Writing and Reading Competitions 4) Public Lectures and Seminars 5) Workshops 6 ) Digital Promotion 7) Video Trailer namely 8) Collaboration 9) Volunteer Program 10) Awarding 11) Social Inclusion Activities. The conclusion of this research is that various activities carried out at the UPT UIN Imam Bonjol Padang Library are aimed at promotion in increasing user interest in utilizing library services and services.